English Phonological Analysis: Revealing Sound Structure and Patterns - Lubis, Yani; Nasution, Sofiyani; Tanjung, Nadila; Wahyuni, Dela; Harahap, Indah Permata Sari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Phonology is a powerful method for deciphering the intricate connection between language and sound structure. Through its investigation, scientists gain bits of knowledge into how sounds are delivered, saw, and coordinated inside dialects, eventually adding to a more profound comprehension of the major idea of human correspondence. In phonology, we experience representative sounds that are mental reflections. They act as portrayals or images that represent the genuine sounds we hear in language. Although they are not exact physical replicas of those sounds, these symbolic sounds are mental constructs that assist us in studying and analyzing how language sounds work. In this study, research methods were utilized. As indicated by Kirk and Mill operator subjective comprehension was at first in light of subjective perceptions as opposed to quantitative perceptions. Phonology is worried about this sort of semantic information. Phonology studies how speech sounds form systems and patterns in human language. Phonetics provides the means for describing a language's phonology, which is the system and pattern of speech sounds.